Advances in Materials and Manufacturing : Selected Peer Reviewed Papers from the International Conference on Advances in Materials and Manufacturing Engineering (ICAMME-2014), December 19-20, 2014, Chennai, India - Palanikumar, K. (Applied mechanics and materials, 2015)
Collection of selected, peer reviewed papers from the International Conference on Advances in Materials and Manufacturing Engineering (ICAMME-2014), December 19-20, 2014, Chennai, India. The 193 papers are grouped as follows: Chapter 1: Hybrid and Composite Materials; Chapter 2: Natural Fibre Composites; Chapter 3: Metal Matrix Composites; Chapter 4: Nano-Scale Materials and Technologies; Chapter 5: Material Characteristics; Chapter 6: Application of Phase Change Materials; Chapter 7: Materials Application and Utilization; Chapter 8: Advances in Coating and Surface; Chapter 9: Advances in Cutting and Machining Processes; Chapter 10: Advances in Welding Process; Chapter 11: Advances in Drilling Process; Chapter 12: Optimization of Processing Technologies; Chapter 13: Numerical Investigations and Algorithms; Chapter 14: Design, Modeling and Simulation; Chapter 15: Applied Mechanics and Mechanical Engineering; Chapter 16: Manufacturing Technology; Chapter 17: Manufacturing Management.